Financial Inclusion in The Fintech Era: Reaching Underserved Communities - Yunike Berry; Sri Lestari Hendrayati (Nomico, 2025)
This study aims to dissect the impact of financial technology (fintech) in broadening financial inclusion across Indonesia, particularly focusing on reaching populations traditionally excluded from conventional banking services. Employing a quantitative research design, data was gathered via surveys from 200 respondents representing diverse societal segments, especially those residing in regions with limited banking access. The findings reveal that fintech exerts a significant positive influence by expanding financial access through user-friendly platforms, expedited processes, and lower costs relative to traditional banking options. Nevertheless, challenges remain, notably the persistent gaps in both financial and digital literacy, which hinder the full adoption of fintech solutions. Additionally, uneven technological infrastructure and public skepticism regarding fintech service security pose substantial barriers. To address these issues, the study advocates for enhanced financial education, the advancement of digital infrastructure, and the strengthening of regulatory frameworks to foster broader and sustainable financial inclusion.